Aplicação dos sistemas de mediação fasorial sincronizada na avaliação da estabilidade de tensão - Raquel Glaucia Freitas da Silva (2010)
This master thesis investigates the Aplication of the Synchronized Phasor Measurement Systems in the Assement of Power System Voltage Stability. The use of this techology enables major advances in Real Time Operation of Eletric Systems, mainly in relation to the dynamic phenomena tracking, such as the Voltage Instability studies have been widespread, there are some questions that must be identified and improved, especialy concerning the identification of the Voltage Stability Margin in real time operation. Aiming to contribute on this subject this work presents an innovate methodology expressed by a consistent and fast index for evaluating such a margin. index indicates to the system's operator the proximity of the critical point related to a monitored bus. This enables preventive actions to be more precise and the re-examination of the margins calculated in the planinnig stage of operation.